2015
DOI: 10.13037/ras.vol13n45.2953
|View full text |Cite
|
Sign up to set email alerts
|

Hipodermóclise: Revisão Sistemática Da Literatura

Abstract: Introdução: A Terapia Subcutânea, também chamada de Hipodermóclise, ainda é pouco discutida e utilizada. Essa técnica consiste na administração de soluções na hipoderme, camada mais profunda da pele, cuja vascularização é similar à que se observa nos músculos. Objetivo: Analisar a produção científica indexada nos periódicos nacionais relacionados ao uso da terapia subcutânea na assistência de Enfermagem. Materiais e Métodos: Optou-se pela revisão sistemática de caráter exploratório com abordagem qualitativa. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
21

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(45 citation statements)
references
References 2 publications
0
24
0
21
Order By: Relevance
“…This lack of knowledge may be associated with a lack of discussion on the subject in schools (15) , a fact that needs to be reviewed, because nursing team knowledge allows reflection on the importance of its role in using this method as a therapeutic resource. Theoretical and practical knowledge about SC therapy can minimize mechanical and tissue trauma, provide comfort, and reduce stress and pain from repeated and unsuccessful punctures for the infusion of fluids and drugs (8) . Change of puncture site every two days.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This lack of knowledge may be associated with a lack of discussion on the subject in schools (15) , a fact that needs to be reviewed, because nursing team knowledge allows reflection on the importance of its role in using this method as a therapeutic resource. Theoretical and practical knowledge about SC therapy can minimize mechanical and tissue trauma, provide comfort, and reduce stress and pain from repeated and unsuccessful punctures for the infusion of fluids and drugs (8) . Change of puncture site every two days.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Paraná (3) showed that only 0.02% of the patients used hypodermoclysis at the institution. Therefore, it is necessary to consider that drug administration is one of the care functions performed, most times, by the nursing team; consequently, it is essential to disseminate information to and train this team (8) . Hypodermoclysis is considered a simple, safe, and effective practice for hydroelectrolytic replacement and/or drug therapy in patients who require clinical treatment in a hospital or home setting (1)(2)(3)22) .…”
Section: / Switzerlandmentioning
confidence: 99%
See 3 more Smart Citations